An earth-abundant and multifunctional Ni nanosheets array as electrocatalysts and heat absorption layer integrated thermoelectric device for overall water splitting. (February 2019) - Zhao, Lili; Yang, Zhiyuan; Cao, Qing; Yang, Linjing; Zhang, Xiaofei; Jia, Jin; Sang, Yuanhua; Wu, Hsin-Jay; Zhou, Weijia; Liu, Hong
Abstract: Hydrogen evolution reaction (HER) from water electrolysis is a promising route for hydrogen fuel production. However, an effective conversion technology from distributed energy resources, such as solar energy and thermal energy, to hydrogen energy is still a challenging research. Here, earth-abundant and multifunctional Ni nanosheets array as electrocatalysts and light absorption layer integrated thermoelectric (TE) device for overall water splitting was proposed. Instead of the traditional power source, the output voltage from thermoelectric (TE) device was directly used for water splitting. More importantly, the structural, photothermal transformation and electrocatalytic characterizations confirmed that the earth-abundant and multifunctional Ni nanosheets array grown on the hot side of TE device was not only as an efficient photothermal conversion layer for providing temperature difference (ΔT) of TE, but also as an active electrocatalysts for HER. The Electrolyzer-TE hybrid devices were designed for overall water splitting in a two-electrode configuration, which possessed high hydrogen production rate of 1.818 mmol/h and oxygen production rate of 0.912 mmol/h. The proposed integrative TE device herein offered great advantages in terms of designing the overall water splitting system, which are helpful for its practical applications for utilization of solar thermal and waste heat. Graphical abstract: Highlights: Ni nanosheets array served as both the photothermal conversion layers and the active electrocatalysts for HER. Multifunctional Ni nanosheets array integrated thermoelectric (TE) device. Electrolyzer-TE hybrid devices were designed for overall water splitting.